A comparative study of early and delayed cord clamping in term deliveries - Gonnade, Nikita V.; Nikhate, Surendra D.; Bal, Himadri; Shrivastava, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Timing of clamping of the umbilical cord has always been a debatable issue. Early cord clamping (ECC) is defined as clamping of the cord within 30 seconds of delivery of the baby and delayed cord clamping (DCC) is defined as clamping of the cord between 30 to 120 seconds of delivery. Delayed cord clamping, despite some limitations, is said to be beneficial to the neonate. A comparative study between ECC and DCC was carried out on a select group of term pregnant women without any high-risk factor and delivering at term. Aim of the study was to compare the effects of early versus delayed cord clamping on neonates and mothers. The focus was on the neonatal haemoglobin levels and adverse effects, if any on neonates and mothers in the two groups. Methods: 100 women satisfying the inclusion/exclusion criteria were recruited for the study. They were randomly divided into two groups of 50 each. Group A underwent early cord clamping and Group B delayed cord clamping. Mothers were observed for 1 hour post-delivery for any evidence of post-partum haemorrhage. Neonates were observed for any sign of tachypnea and blood sample was sent after 72 hours of delivery for analyzing Hb, hematocrit and bilirubin of the neonate. Results: The results revealed that neonates with DCC had a higher mean Hb level of 15.02 vis-à-vis the ECC group Hb of 11.69G/dl and the difference was statistically significant. Similarly mean hematocrit of DCC group was 48.67 while the ECC group mean was 42.36, the difference again was statistically significant. There was no significant side effects or complications in both mother and newborn babies. Conclusions: It was concluded that delayed cord clamping should be practiced in otherwise non high-risk deliveries.